Psychological repercussions of PM air pollution in human aging: a comprehensive review of urban and rural environments - Gallardo, Laura O.; Aiger Vallés, Montserrat; Cativiela-Campos, Blanca; Domingo-Valero, Laura; Barrasa, Ángel; Alique, Matilde; López-Granero, Caridad (Frontiers in Pharmacology, 2025)
Air pollution and its effects on population health are currently among the most important public health issues. It is well established that the impact of air pollution on health is exceedingly high, although it ignores its real scope and effects on the aging process because studies on air quality have largely focused on younger age groups. Herein, we emphasize the relevance of air quality to the behavioral aging process, taking into account the place of residence - rural or urban. We raise the following question: Can air quality and residential settings modulate cognitive, emotional and social behaviors during the aging? Some studies have analyzed the role of residential settings and air pollution in the context of a behavioral frame in elderly people. Based on the analyzed literature, this revision concluded that air pollutants affect cognitive function, increasing the risk of dementia as well as depression and anxiety emotional responses. In addition, social networks and inclusion can modulate and mitigate the effects observed during the aging in rural areas that are exposed to less contamination. Although there is no consensus, it seems that some observed behavioral effects are sex-dependent, as women are more vulnerable to air pollution. Additionally, we examined why older adults are vulnerable to the health effects of Particulate Matter (PM) exposure and highlighted the importance of social health in this context. Environmental agents could be the key to understanding the susceptibility and variability observed during aging in behavioral symptoms. Although cognitive decline is related to increased age, it is not a manipulated factor. Efforts should be centered on locating factors implicated in the aging process that could be susceptible to manipulation or variation, such as the choice of the place of residence and the air that we are breathing. Given the significant societal impact of PM, research and policy regulations should be closely aligned and collaborative.